Influence of CeO2 layer thickness on the properties of CeO2/Gd2O3 multilayers prepared by pulsed laser deposition. (March 2015) - Mishra, Maneesha; Kuppusami, P.; Reddy, V.R.; Ghosh, C.; Divakar, R.; Ramaseshan, R.; Singh, Akash; Thirumurugesan, R.; Mohandas, E.
Abstract: CeO2 /Gd2 O3 multilayers were prepared on Si (100), quartz and inconel-783 substrates by pulsed laser deposition technique at an oxygen partial pressure of 2 Pa and substrate temperatures of 300 and 873 K. The layer thickness of CeO2 was varied from 5 to 30 nm, whereas Gd2 O3 layer thickness was kept constant (∼10 nm). The phase and crystallite size of the films were characterized by X-ray diffraction (XRD), X-ray reflectivity (XRR), Raman spectroscopy, atomic force microscopy (AFM) and high resolution transmission electron microscopy (HRTEM) techniques. The layer thicknesses, measured by XRR as well as from HRTEM micrographs were in good agreement with each other. The CeO2 /Gd2 O3 multilayers show transmittance of ∼70%. Nanoindentation measurements indicated that the hardness values of the multilayers were higher than that of single layers of CeO2 and Gd2 O3 thin films. Highlights: CeO2 /Gd2 O3 multilayers were deposited by pulsed laser deposition technique. Formation of cubic phases of CeO2 and Gd2 O3 were observed. The multilayers show good transmittance of ∼70%. Band gap value increases with increase in the substrate temperature and layer thickness of CeO2 . Nanomechanical properties of the multilayers were found to be higher than that of single layers.